IECEC 96. Proceedings of the 31st Intersociety Energy Conversion Engineering Conference
DOI: 10.1109/iecec.1996.553380
|View full text |Cite
|
Sign up to set email alerts
|

Constant slip control of induction motor at light load

Abstract: The most widely used AC motor drives adopt Rated Flux Control (RFC) method. However, at light load condition, RFC causes excessive iron loss, thus the conversion efficiency of the drive system impaired. This paper introduces a new control approach -Constant Slip Control (CSC), which minimize the stator current at light load, so that the iron loss and reactive power consumption of the motor are decreased. Simulation results compare the power consumption of CSC with that of W C in order to validate the theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Therefore, operation at optimal efficiency can be achieved by acting on the reference flux. Several reports [15][16][17][18][19][20][21][22][23][24][25][26] have already been conducted aiming to reduce the power losses in induction motor drive. Based on the ways employed to reach the objective, efficiency optimization methods can be grouped into simple control, model-based control, search control, hybrid method (combination of modelbased control and search control).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, operation at optimal efficiency can be achieved by acting on the reference flux. Several reports [15][16][17][18][19][20][21][22][23][24][25][26] have already been conducted aiming to reduce the power losses in induction motor drive. Based on the ways employed to reach the objective, efficiency optimization methods can be grouped into simple control, model-based control, search control, hybrid method (combination of modelbased control and search control).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was observed in [9] that the variation of power factor is small when efficiency is optimal such that it can be considered constant. As alternate to power factor, in [17,18] it has been demonstrated that optimal efficiency is maintained when the motor is operated at constant slip determined only from motor parameters. The disadvantage of this approach is that the accuracy of this method is limited to a narrow set of conditions for use and there could be shift of optimal operating point due to parameter variations.…”
Section: Introductionmentioning
confidence: 99%